Prediction of the Gas Injection Effect on the Asphaltene Phase Envelope - Bahrami Peyman (Oil & Gas Science and Technology, 2015)
Asphaltene instability may occur when pressure, temperature and compositional variations affect the reservoir oil. Permeability reduction, wettability alteration, and plugging of wells and flow lines are the consequences of this phenomenon. Therefore, it is crucial to investigate the asphaltene behavior in different thermodynamic conditions by knowing the Asphaltene Precipitation Envelope (APE) in a preventive way rather than the costly clean-up procedures. The selected reservoir oil has faced a remarkable decline in production due to several years of extraction, and Enhanced Oil Recovery (EOR) has been considered as a solution. Therefore, in this paper, a comprehensive study was carried out to predict the effects of different injected gases on asphaltene onset and to prevent future asphaltene precipitation based on the laboratory data. The Advanced Redlich-Kwong-Soave (RKSA) equation of state was considered to develop APE using Multiflash (Infochem Co.). For the selected reservoir oil, with temperature reduction at low temperatures, asphaltene precipitation weakened and made the onset pressure decrease, so this behavior is different from the results obtained in other published reports. On the basis of this model, several sensitivity analyses were performed with different gases (i.e., methane, CO2, N2 and associated gases) to compare the risk of each gas for future EOR strategies. APE tend to expand as the amount of injected gases increases, except for CO2 gas injection, that showed another unconventional behavior for this crude oil. It was observed that for CO2 gas injection below a certain temperature, asphaltene stability increased, which can be considered as a good inhibitor of asphaltene precipitation.